Repeated trauma exposure does not impair distress reduction during imaginal exposure for posttraumatic stress disorder. Issue 8 (6th December 2016) - Jerud, Alissa B.; Farach, Frank J.; Bedard‐Gilligan, Michele; Smith, Hillary; Zoellner, Lori A.; Feeny, Norah C.
Abstract : Background: Based on experimental research on threat extinction, individuals exposed to repeated traumatic events may have impaired outcome in exposure therapy compared to those who have experienced a single trauma (Lang & McTeague, 2011 ). This study examined whether repeated trauma exposure predicts smaller changes in self‐reported distress during imaginal exposure and worse outcomes for patients with posttraumatic stress disorder (PTSD). Methods: Adults ( N = 116) with chronic PTSD received up to 10 sessions of prolonged exposure (PE) therapy. Trauma exposure was assessed via interview and number of traumatic events were summed for each participant. To examine reductions in distress during treatment, mean and peak values of distress during imaginal exposure were calculated for the first imaginal session (initial distress activation) and subsequent sessions (between‐session change in distress). Change in PTSD symptoms from pre‐ to posttreatment and follow‐up provided an additional index of outcome. Results: In‐session distress during imaginal exposure decreased over the course of treatment. PTSD symptoms also decreased over treatment, with gains being maintained through follow‐up. Repeated trauma exposure was not significantly correlated with initial distress activation. Additionally, linear mixed‐model analyses showed no significant association between repeated trauma exposure and between‐session change in distress or PTSD symptoms. Conclusions: Contrary to recent speculation, repeated trauma exposure did not predict less change in self‐reported distress during imaginal exposure or worse PTSD outcomes. The bench‐to‐bedside linkage of threat extinction to exposure therapy is discussed, noting strengths and weaknesses. Patients with repeated trauma exposure show reductions in distress with exposure treatment and benefit from PE as much as patients with single‐exposure trauma histories.